1
$\begingroup$

I think I understand implicit differentiation outside of those problems involving trig functions but for some reason this problem is breaking my brain:

Assume that y is a function of x. Find $\frac{dy}{dx}$for $x^3+\cos^3(y)=5x$

My first move, using the chain rule, is:
$3x^2+3\cos^2(y)(-\sin(y))=5$

However the text says this should instead be:

$3x^2+3\cos^2(y)(-\sin(y))\frac{dy}{dx}=5$

I don't understand where or how the $\frac{dy}{dx}$ is being introduced.

To my mind, $\cos^3(y)$ = $(\cos(y))^3$ and so could be interpreted as:
$f(x)=x^3$
$g(x)=\cos(y)$
$F(x)=f(g(x))=\cos^3(y)$

Then, using the Chain Rule:
$F'(x)=f'(g(x))\cdot g'(x)=3\cos^2(y)(-\sin(y))$

But apparently that's wrong.

Thanks in advance.

$\endgroup$
2
$\begingroup$

by the chaine rule we get $3x^2+3\cos(y(x))^2(-\sin(y(x))\cdot y'(x)=5$

$\endgroup$
  • $\begingroup$ So we can read $cos^3(y)$ as $cos^3(y(x))$? $\endgroup$ – Nick Oct 18 '14 at 17:04
  • $\begingroup$ yes since $y=y(x)$ $\endgroup$ – Dr. Sonnhard Graubner Oct 18 '14 at 17:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.